Inscriptions on the steps and platform of the Mandakini Kund - Temples of India Project Team (Jio Institute, 2024)
On the steps and platform of the Mandakini Kund, several inscriptions are discovered in various states of preservation. These inscriptions are written in the Sanskrit language using the Devanagari script. A thorough examination of these inscriptions reveals valuable information, including the name of the temple, Mahakal, and the designation of the reservoir as Mandakini. Additionally, they provide details such as the date of the devotees' visit and their community affiliation. The inscriptions mention the worshipers' practice of visiting the Mahakal Temple and bathing in the Mandakini Kund. Dating from the 13th to the 15th centuries CE, some of these inscriptions specifically mention members of the Kayastha Mathur community.